Evaluation of safe periods for germination of a few vegetable crops - SASTRY , P. S. N.; VICTOR, U. S. (MAUSAM, 1976)
Soil temperature is an important critical factor for germination of vegetable seed. Utilising daily soil temperature data recorded on the sandy loam soils of Delhi for 16 years from 1955-70,a method has been described to delineate favourable period for seed germination of cabbage ,carrot onion and peas varieties of varied tolerance to unfavourable soils temperature .It is suggested that by following suitable agronomies practices like irrigation and mulching the seedling period could be extended by a few week .